Pertanggungjawaban Hukum Penjual Akibat Pembatalan Perjanjian Pengikatan Jual Beli Tanah - Rocky Bayakta Brahmana; Rayani Saragih; Maslon Hutabalian (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the legal liability of a seller toward a buyer following the cancellation of a Sale and Purchase Binding Agreement (PPJB), as well as the factors leading to such cancellation by the seller. The research employs an empirical juridical method, examining applicable legal provisions alongside their practical application in the field. Data were gathered through both literature reviews and field studies. The literature review involved analyzing primary legal sources—specifically Articles 1320, 1243, and 1338 of the Indonesian Civil Code—as well as secondary sources (journals, research findings, and expert legal opinions) and tertiary sources (dictionaries, internet resources, and scholarly journals). Fieldwork was conducted via direct interviews at the office of PPAT/Notary Carolla Sembiring. The collected data were analyzed qualitatively using a descriptive-analytical method. The findings indicate that a seller incurs legal liability toward the buyer if they unilaterally cancel the PPJB without a valid reason. Such an action constitutes a breach of contract, as it contravenes Articles 1320 and 1338 of the Civil Code, which stipulate that legally formed agreements serve as law for the parties who entered into them. The legal consequence of this cancellation is that the seller is obligated to refund all payments received from the buyer and may be held liable for damages to compensate for the losses suffered by the buyer.